A multicomponent quality improvement intervention to improve blood pressure and reduce racial disparities in rural primary care practices. Issue 4 (25th November 2016) - Cené, Crystal W.; Halladay, Jacqueline R.; Gizlice, Ziya; Donahue, Katrina E.; Cummings, Doyle M.; Hinderliter, Alan; Miller, Cassandra; Johnson, Larry F.; Garcia, Beverly; Tillman, Jim; Little, Edwin P.; Rachide, Marjorie R.; et al.
Abstract : The Southeastern United States has the highest prevalence of hypertension and African Americans have disproportionately worse blood pressure control. The authors sought to evaluate the effect of a multicomponent practice‐based quality improvement intervention on lowering mean systolic blood pressure (SBP) at 12 and 24 months compared with baseline among 525 patients, and to assess for a differential effect of the intervention by race (African Americans vs white). At 12 months, both African Americans (−5.0 mm Hg) and whites (−7.8 mm Hg) had a significant decrease in mean SBP compared with baseline, with no significant between‐group difference. Similarly, at 24 months, mean SBP decreased in both African Americans (−6.0 mm Hg) and whites (−7.2 mm Hg), with no significant difference between groups. Notably, no significant racial disparity in mean SBP at baseline was shown. The intervention was effective in lowering mean SBP in both African Americans and whites but there was no differential effect of the intervention by race.